2023
DOI: 10.3389/fgene.2023.998035
|View full text |Cite
|
Sign up to set email alerts
|

Association between autophagy and acute pancreatitis

Abstract: Autophagy pathway involves maintaining intracellular homeostasis by regulating the degradation of cytoplasmic components. Disfunction of autophagic process has been confirmed to be critical mechanism in many diseases, including cancer, inflammation, infection, degeneration and metabolic disorders. Recent studies have shown that autophagy is one of the early events in acute pancreatitis. Impaired autophagy promotes the abnormal activation of zymogen granules and results in apoptosis and necrosis of exocrine pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Dysfunction of the autophagy process has been proven to be a key mechanism in many diseases, including cancer, inflammation, infection, degeneration, and metabolic disorders 20 . Recent studies have indicated that autophagy is one of the early events in acute pancreatitis 21 . Impaired autophagy can promote abnormal activation of zymogen granules, leading to apoptosis and necrosis of exocrine pancreatic cells 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunction of the autophagy process has been proven to be a key mechanism in many diseases, including cancer, inflammation, infection, degeneration, and metabolic disorders 20 . Recent studies have indicated that autophagy is one of the early events in acute pancreatitis 21 . Impaired autophagy can promote abnormal activation of zymogen granules, leading to apoptosis and necrosis of exocrine pancreatic cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that autophagy is one of the early events in acute pancreatitis 21 . Impaired autophagy can promote abnormal activation of zymogen granules, leading to apoptosis and necrosis of exocrine pancreatic cells 21 . Furthermore, it was found that the SQSTM1 (sequestosome 1) in the serum of AP patients is significantly increased, and additional study revealed that the intracellular SQSTM1 protein increased the expression of ACSL4 in a manner dependent on the receptor for advanced glycation end products (AGER), leading to the production of polyunsaturated fatty acids, inducing autophagosome formation, and subsequently causing ferroptosis, exacerbating the course of AP 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that AP may rely on the theory of the activated pathway of lysosome and autophagy ( 17 ). Naturally, the easiest pathophysiological mechanism represents ischemia of pancreatic tissue leading to dysregulated enzymatic activities ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In light of the role of insulin in the AP pathophysiology due to the hypertriglyceridemia state as the known risk factor for AP development, defective pancreatic cells contribute to insulin deficiency ( 15 ). Insulin is proven to decrease the hypertriglyceridemia state and in that way acts as a preventive care measure in terms of pancreatic parenchymal preservation ( 1 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent acute pancreatitis increases the risk of developing chronic pancreatitis, and survivors experience reduced long-term quality of life [ [17] , [18] , [19] ]. Core events in acute pancreatitis pathogenesis include pathological calcium signaling, mitochondrial dysfunction, premature activation of proteolytic enzymes, endoplasmic reticulum stress, impaired unfolded protein response, and impaired autophagy [ [20] , [21] , [22] , [24] , [25] , [26] , [27] [20–22,24–27, 23 ]. Inhibition of nuclear factor-kappaB activation, NLRP3 inhibition, restoration of mitochondrial and/or autophagic function, ORAI1 inhibition, inhibition of the RIP1-RIP3 pathway, TNF-alpha inhibition, autophagy pathway inhibition, TLR4 expression suppression, and oxidative stress inhibition have emerged as potential targets or pathways for acute pancreatitis treatment [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] ].…”
Section: Introductionmentioning
confidence: 99%